Fractal Approach to Tribology of Elastomers - Janahmadov, Ahad Kh.; Javadov, Maksim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book summarizes the results of years of research on the problem of strength and fracture of polymers and elastomers. It sets out the modern approach to the strength theory from the standpoint of fractals, the kinetic and thermodynamic theories as well as the meso-mechanic destruction. The dimension reduction method is applied to model the friction processes in elastomers subjected to the complex dynamic loading. Finally, it analyses a relation between the fracture mechanism and the relation phenomena, and provides new experimental data on the sealing nodes in accordance with their specific working conditions where the effect of self-sealing is observed.
About theoretical strength of materials -- General laws of friction and wear of polymers -- Fractal kinetics of fracture -- Modern problems of frictional contacts of elastomers -- Dimension reduction as modeling method for elastomers under complex dynamic loading -- General problems of sealing units and their classifications -- Stress-strain state of sealants of complex shapes -- Sealing properties of elastic element.
Keywords: Coatings; Tribology; Corrosion and anti-corrosives.; Mechanics, Applied; Solids; Polymers; Condensed matter; Coatings; Tribology; Corrosion; Solid Mechanics; Polymers; Condensed Matter Physics